Family economic hardship and adolescent mental health during the COVID-19 pandemic - Kim, Bomgyeol; Kim, Do Hee; Jang, Suk-Yong; Shin, Jaeyong; Lee, Sang Gyu; Kim, Tae Hyun (Frontiers in Public Health, 2022)
Objective: This study examined whether pandemic related family economic hardships influenced adolescents’ mental health during the COVID-19 pandemic in Korea. Methods: Data were collected from 54,948 adolescents who participated in the 2020 Korea Youth Risk Behavior Web-Based Survey. We performed a multiple logistic regression analysis to examine the association between family economic hardship and mental health (anxiety, depressive symptoms, and suicidal ideation). Results: Among the adolescents, 39.7%, 24.7%, and 5.9% reported slight, moderate, and severe economic hardship, respectively. COVID-19 related family economic hardship was significantly associated with higher odds of adolescents reporting anxiety, depressive symptoms, and suicidal ideation. This association was stronger among adolescents with low to middle family economic status. Conclusions: This study suggests that adolescents from more economically vulnerable families are likely to be at a higher risk for long-term mental health effects due to the financial consequences of the COVID-19 pandemic.